2013
DOI: 10.3390/en6073481
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Novel Method for Corrosion Studies of Electroplated Lithium Metal Based on Measurements with an Impedance Scanning Electrochemical Quartz Crystal Microbalance

Abstract: Abstract:A new approach to study the chemical stability of electrodeposited lithium on a copper metal substrate via measurements with a fast impedance scanning electrochemical quartz crystal microbalance is presented. The corrosion of electrochemically deposited lithium was compared in two different electrolytes, based on lithium difluoro(oxalato) borate (LiDFOB) and lithium hexafluorophosphate, both salts being dissolved in solvent blends of ethylene carbonate and diethyl carbonate. For a better understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Numerous fluorinated borate based salts have been fabricated including LiBFMB 57,127 and LiD-FOB. 50,116,128 Both of these Li salts have much higher solubility in carbonate solvents than LiBOB and Li transference numbers greater than LiPF 6 (t Li+ = 0.47 LiBFMB; 0.33 LiDFOB; 0.24 LiPF 6 ). 127 Schedlbauer et al reported a study of the cyclability of Li in LiPF 6 and LiDFOB electrolytes, 129 and found that the LiDFOB electrolytes had much higher Coulombic efficiencies compared to LiPF 6 upon cycling, 95-97% vs. 75% after 500 cycles.…”
Section: Li-salts For Li-metal Batteriesmentioning
confidence: 99%
“…Numerous fluorinated borate based salts have been fabricated including LiBFMB 57,127 and LiD-FOB. 50,116,128 Both of these Li salts have much higher solubility in carbonate solvents than LiBOB and Li transference numbers greater than LiPF 6 (t Li+ = 0.47 LiBFMB; 0.33 LiDFOB; 0.24 LiPF 6 ). 127 Schedlbauer et al reported a study of the cyclability of Li in LiPF 6 and LiDFOB electrolytes, 129 and found that the LiDFOB electrolytes had much higher Coulombic efficiencies compared to LiPF 6 upon cycling, 95-97% vs. 75% after 500 cycles.…”
Section: Li-salts For Li-metal Batteriesmentioning
confidence: 99%
“…[15][16][17][18] However, corrosion of aluminum is observed in this same potential range for other electrolyte salts. [19][20][21] Many different types of carbon additives have been utilized in cathode laminates and differences in the physical properties such as surface area and porosity affect stability and performance. [22][23][24][25][26][27][28] However, studies of carbon additives at high potential (>4.6 V) are limited and typically have been investigated in the presence of active materials.…”
mentioning
confidence: 99%
“…[23][24][25] An example is the recent EQCM analysis of heavily damped systems such as metal foils adhered to an electrode mounted on a quartz crystal. 36,37 Those two publications interpreted frequency changes gravimetrically, correlating frequency increases to mass decreases and vice versa. Our nanofoam results are also interpreted gravimetrically, but we do not assign mass values because of the thickness (∼100 μm) and varying porosity of these electrodes.…”
Section: Resultsmentioning
confidence: 99%